A hardware efficient parallel Viterbi algorithm - Black, P.J.; Meng, T.H.-Y. (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 1990)
A hardware efficient block processing scheme is proposed for concurrent implementation of the Viterbi algorithm. The throughput increase is proportional to the increase in hardware complexity at the expense of latency. Advantages of the algorithm over other parallel schemes are that the reduction of the information rate due to bit stuffing at the transmitter and extraction of block synchronization from the received data are not necessary. The scheme is well suited to the problem of sequence estimation in the presence of intersymbol interference, although it can be applied to any decoder based on the Viterbi algorithm.< >